Why Does Intellectual Disability Matter to Philosophy?: Toward a Transformative Pedagogy - Carlson, Licia (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
This article explores what it means to include intellectual disability (ID) in philosophical discourse and in the philosophy classroom. Taking Audre Lorde’s claim that “the master’s tools will never dismantle the master’s house” as a starting point, it asks how certain forms of cognitive ableism have excluded ID from the “philosopher’s house.” Drawing upon Michel Foucault’s work as a theoretical framework, part one critically examines the ways that ID has been included, excluded, and constructed within philosophical discourse. Part two then considers what it would mean for ID and people with an ID to be included in the philosophy classroom. It offers some examples of how the work in disability studies, philosophies of disability, and philosophy of art can lead to a more inclusive and transformative pedagogy that will generate new critical questions and expand our philosophical dwelling places.